Legal Framework for the Prevention and Eradication of Money Laundering as an Instrument for Countering Terrorism Financing (Lex Journal : Kajian Hukum dan Keadilan, 2023)
This study examines the synchronization and effectiveness of the legal framework for the prevention and eradication of money laundering (Tindak Pidana Pencucian Uang/TPPU) as an instrument for countering terrorism financing (Tindak Pidana Pendanaan Terorisme/TPT) within Indonesia's criminal law system. Employing a normative juridical research method, this study applies Hans Kelsen's Hierarchy of Norms Theory to analyze legal synchronization, and Lawrence M. Friedman's Legal System Theory to evaluate effectiveness across the dimensions of legal substance, legal structure, and legal culture. The findings reveal that the legal framework governing TPPU and TPT suffers from significant inconsistencies both vertically and horizontally. Vertical synchronization discloses misalignments between statutes and their implementing regulations concerning definitions, scope, and implementation mechanisms. Horizontal synchronization exposes inconsistencies in the formulation of criminal elements and evidentiary standards between Law No. 8 of 2010 on Money Laundering and Law No. 5 of 2018 on the Eradication of Terrorism, despite terrorism having been formally recognized as a predicate crime under the former. Furthermore, the effectiveness of the TPPU legal framework as a counter-terrorism financing instrument is constrained across all three dimensions of Friedman's legal system. From the substantive dimension, the money laundering legal construction is insufficiently compatible with the forward-looking nature of terrorism financing, which characteristically involves legitimate funds directed toward illegal purposes. From the structural dimension, institutional fragmentation and weak inter-agency coordination undermine the optimal functioning of the Indonesian Financial Intelligence Unit (PPATK). From the cultural dimension, low public awareness, limited enforcement capacity, and underdeveloped private sector compliance culture collectively impede effective early detection and risk-based approach implementation.